Empowering Mothers in 'Lek Anak Nagari' Through Digitalization: A Case Study - Karlinda, Karlinda; Nurcihikita, Tiara; Putri, Wanda Luthfiani Dwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Indonesia is in fourth place with the largest number of children (85 million people). The standard for stunting cases set by the Ministry of Health is 14%. Jambi province, especially Muara Bungo district, has a stunting incidence rate of 14.4%, meaning that there are 0.4% of cases that exceed the standards set by the Ministry of Health. This research aims to examine the influence of maternal empowerment (knowledge, attitudes (parenting patterns), technological adaptation, nutritional innovation in preventing stunting in Tuo Lubuk Mengkuang hamlet, Jambi. This research uses a quantitative research design with a case study approach. Technique Data collection used observation, questionnaires and interviews. Data analysis used was univariate analysis and bivariate analysis (Dependent T-Test. There was no relationship = 0.449) on the incidence of stunting, and there was a significant relationship between parenting attitudes. p= 0.049; OR= - 1.50) and technology adaptation status (p=0.041; OR= 1.38), maternal education (p= <0.001) on the incidence of stunting. Assistance with technology adaptation, parenting style status, and education for mothers influence the incidence of stunting (not good nutritional status) in children in Tuo Lubuk Mengkuang Hamlet, Jambi.